Passive Repetitive Stretching for a Short Duration within a Week Increases Myogenic Regulatory Factors and Myosin Heavy Chain mRNA in Rats' Skeletal Muscles - Yurie Kamikawa; Satoshi Ikeda; Katsuhiro Harada; Akihiko Ohwatashi; Akira Yoshida (The Scientific World Journal)
Stretching is a stimulation of muscle growth. Stretching for hours or days has an effect on muscle hypertrophy. However, differences of continuous stretching and repetitive stretching to affect muscle growth are not well known. To clarify the difference of continuous and repetitive stretching within a short duration, we investigated the gene expression of muscle-related genes on stretched skeletal muscles. We used 8-week-old male Wistar rats () for this study. Animals medial gastrocnemius muscle was stretched continuously or repetitively for 15 min daily and 4 times/week under anesthesia. After stretching, muscles were removed and total RNA was extracted. Then, reverse transcriptional quantitative real-time PCR was done to evaluate the mRNA expression of MyoD, myogenin, and embryonic myosin heavy chain (MyHC). Muscles, either stretched continuously or repetitively, increased mRNA expression of MyoD, myogenin, and embryonic MyHC more than unstretched muscles. Notably, repetitive stretching resulted in more substantial effects on embryonic MyHC gene expression than continuous stretching. In conclusion, passive stretching for a short duration within a week is effective in increasing myogenic factor expression, and repetitive stretching had more effects than continuous stretching for skeletal muscle on muscle growth. These findings are applicable in clinical muscle-strengthening therapy.